Present Status and Long-Term Changes of Water Quality Characteristics in Heavily Polluted Mediterranean Lagoon, Lake Mariut, Egypt - H.H. Ali, Mohamed; Abdel-Satar, Amaal M.; El-Sherif M. Goher., Mohamed (IJRDO-Journal of Applied Science, 2017)
The present status, a long term change of water quality characteristics besides metal pollution load (Fe, Mn, Zn, Cu and Cd) in water of a heavily polluted Mediterranean Lake (Mariut Lake northwest of Egypt) were investigated. Water quality characteristics varied in a wide range among the different basins. Depending on collecting data; the agricultural and domestic sewage drained from Al-Qalaa Drain responsible for the most drastic deterioration status in main basin of the lake. Meanwhile, Aquaculture Basin has the highest values of salinity and consequently both major cations and anions. Ratio of N:P indicated of potential N limits on phytoplankton growth. Almost, the values of all studied metals are higher than standard permissible levels. The contamination index (Cd) revealed that the order of pollution increasing as WB < SB < AQB < MB. PCA analyses showed that most of nutrient salts associated with heavy metals were responsible for heavily polluted zones. Cluster analyses showed that, main basin has the most polluted aspects depending on concentration of studying parameters followed by a moderate polluted aquaculture basin then low polluted western and southern basins.